Habituation without NMDA Receptor-Dependent Desensitization of Hering–Breuer Apnea Reflex in a Mecp2+/− Mutant Mouse Model of Rett Syndrome - Song, Gang; Tin, Chung; Giacometti, Emanuela; Poon, Chi-Sang (Frontiers in Integrative Neuroscience, 2011)
Non-associative learning is a basic neuroadaptive behavior exhibited in almost all animal species and sensory modalities but its functions and mechanisms in the mammalian brain are poorly understood. Previous studies have identified two distinct forms of non-associative learning in the classic Hering–Breuer inflation reflex (HBIR) induced apnea in rats: NMDA receptor (NMDAR)-independent habituation in a primary vagal pathway and NMDAR-dependent desensitization in a secondary pontine pathway. Here, we show that abnormal non-associative learning of the HBIR may underlie the endophenotypic tachypnea in an animal model of Rett syndrome (RTT), an autism-spectrum disorder caused by mutations in the X-linked gene encoding methyl-CpG-binding protein 2 (MECP2). Mecp2+/− symptomatic mice on a mixed-strain background demonstrated significantly increased resting respiratory frequency with shortened expiration and normal inspiratory duration compared with asymptomatic mutants and wild-type controls, a phenotype that is characteristic of girls with RTT. Low-intensity electrical stimulation of the vagus nerve elicited fictive HBIR with time-dependent habituation in both Mecp2+/− and wild-type mice. However, time-dependent desensitization of the HBIR was evidenced only in wild-type controls and asymptomatic mutant mice but was absent or suppressed in Mecp2+/− symptomatic mice or in wild-type mice after blockade of NMDAR with dizocilpine. Remarkably, ∼50% of the Mecp2+/− mice developed these X-linked phenotypes despite somatic mosaicism. Such RTT-like respiratory endophenotypes in mixed-strain Mecp2+/− mice differed from those previously reported in Mecp2-/y mice on pure C57BL/6J background. These findings provide the first evidence indicating that impaired NMDAR-dependent desensitization of the HBIR may contribute to the endophenotypic tachypnea in RTT.